Protect children’s rights from cyberviolence under the Vietnamese law - Lâm, Tố Trang (International Journal of Innovative Research and Scientific Studies, 2025)
The rapid development of the internet and social networks brings many benefits and supports information and communication. However, the explosion of information technology, in addition to its positive aspects, has raised many issues related to the current network environment. In the era of strong development of the internet and artificial intelligence today, cyber violence is occurring in a complicated manner on a global scale. Because children are vulnerable to fraud, exploitation, and even abuse through internet platforms, protecting children from violence in cyberspace is always a matter of concern for many countries, including Vietnam, one of the countries with the most internet users in the world. This research introduces the age of children in international legal documents and under Vietnamese law and at the same time presents the concept and forms of violence in cyberspace today. This article also analyzes the current legal framework in Vietnam, from the responsibility to protect children’s rights in cyberspace to handling acts of violence against children in cyberspace, thereby proposing some related recommendations.